2019
DOI: 10.1080/09640568.2019.1663723
|View full text |Cite
|
Sign up to set email alerts
|

Disconnected dots?: A systematic review of governance challenges for natural resource management

Abstract: As concerns for the ongoing and increasing degradation of the natural environment worldwide, have increased the impetus for action, and development of governance arrangements to support natural resource management. Despite this, issues around governance remain a significant challenge to the success of natural resource management. This study reports the findings of a systematic literature review of 240 papers to better understand how governance challenges manifest spatially, how they change over time, and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
2
8
0
Order By: Relevance
“…Our review showed that challenges related to responsive environmental governance were the least dominant. The limited number of articles identified in the review is also similar to the trends identified by Potts (2020) in a global review of governance challenges. This might mean that responsive environmental governance challenges are understudied or not considered to be core challenges (Potts 2020).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our review showed that challenges related to responsive environmental governance were the least dominant. The limited number of articles identified in the review is also similar to the trends identified by Potts (2020) in a global review of governance challenges. This might mean that responsive environmental governance challenges are understudied or not considered to be core challenges (Potts 2020).…”
Section: Discussionsupporting
confidence: 52%
“…The limited number of articles identified in the review is also similar to the trends identified by Potts (2020) in a global review of governance challenges. This might mean that responsive environmental governance challenges are understudied or not considered to be core challenges (Potts 2020). Other understudied areas within southern Africa include social-ecological stewardship, polycentricity, innovation and experimentation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…For example, Ozerol et al (2018) conducted the SLR to assess how water governance is conceptualised, contextually defined, and evaluated in different parts of the world. Similarly, Eckhardt et al (2019) and Potts (2019) applied the SLR method to assess the governance issues for natural resource management. Another study (Brisbois & De Loë, 2015) examined the use of collaborative strategies for governing water resources using a formal systematic review.…”
Section: Methodsmentioning
confidence: 99%